The Impact of CAMELS on Banks’ Credit in Cambodia: A Two-Step GMM Method - Mong, Mara (Journal of Ecohumanism, 2025)
The aim of this research was to examine the components of the CAMELS framework, which encompasses capital adequacy, asset quality, management quality, earnings quality, liquidity, and sensitivity to market risk, as utilized by the central bank to assess the health of banks. To address this objective, a research question was formulated: Do all components of CAMELS significantly influence the credit growth of banks? To answer this question, a dynamic panel data model was employed, utilizing a two-step GMM approach. This model not only included the CAMELS variables but also integrated three macroeconomic indicators: the growth rate of real GDP, money supply, and government spending. The empirical results indicated that capital adequacy and earnings quality significantly affected credit growth, while asset quality, management quality, and sensitivity to market risk negatively impacted banks’ credit. Additionally, the findings revealed that the growth of real GDP and money supply positively contributed to credit growth, whereas the relationship between government spending growth and banks’ credit was found to be insignificant.